Emergency frequency control strategy of distribution system based on the coordination of multi-resource - Shen, Zeyuan; Wang, Chao; Wang, Yao; Zhao, Haibo; Wu, Zhong; Hu, Ende (Frontiers in Energy Research, 2023)
The urban distribution system is pivotal in ensuring efficient power distribution within urban areas. In recent years, the rising frequency and intensity of extreme events have posed significant challenges to the reliable operation of urban distribution systems. While substantial research exists on emergency frequency control strategies for large-scale power grids, there needs to be more attention to addressing the emergency frequency control challenges that arise when the urban distribution system becomes isolated from the superior power grid due to extreme events. This paper seeks to enhance the system's resilience and ability to withstand extreme events by investigating the coordinated regulation of synchronous generators, wind farms, battery energy storage systems, temperature control loads, and conventional load resources within the urban distribution system. To this end, we first establish a reduced-order model for the multi-resource system's frequency response. Then, the analytical expressions of the lowest point of the system frequency, the lowest point time, and the quasi-steady state frequency are derived. Aiming at the problem of multi-resource coordinated regulation, an emergency frequency control strategy considering the system safety frequency constraint, resource control amount constraint, and line power flow constraint is proposed. To validate the proposed method, implement simulations using the MATLAB/Simulink platform and consider IEEE 13 bus and IEEE 33 bus distribution systems as test cases. The simulation results show that the method effectively regulates the resources in the distribution system, effectively reducing frequency deviation, ensuring that the lowest frequency remains within the safety threshold of not less than 49.8Hz, and the quasi-steady state frequency is higher than 49.8Hz. Moreover, the proposed method minimizes control costs and limits load-shedding, thereby fully leveraging the capabilities of the diverse resources present in the urban distribution system.